2012
DOI: 10.1002/humu.22139
|View full text |Cite
|
Sign up to set email alerts
|

Absence ofFKBP10in recessive type XI osteogenesis imperfecta leads to diminished collagen cross-linking and reduced collagen deposition in extracellular matrix

Abstract: Recessive osteogenesis imperfecta (OI) is caused by defects in genes whose products interact with type I collagen for modification and/or folding. We identified a Palestinian pedigree with moderate and lethal forms of recessive OI caused by mutations in FKBP10 or PPIB, which encode endoplasmic reticulum resident chaperone/isomerases FKBP65 and CyPB, respectively. In one pedigree branch, both parents carry a deletion in PPIB (c.563_566delACAG), causing lethal type IX OI in their two children. In another branch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 44 publications
(59 reference statements)
5
94
0
3
Order By: Relevance
“…Figure 6C and 6D) as well as in decreased secreted collagen (Figure 8). In line with our results, deficiency of FKBP10 in osteogenesis imperfecta has been shown to attenuate collagen secretion and, moreover, decrease the extent of lysyl hydroxylation and extracellular collagen cross-linking and increase protease sensitivity of extracellular collagen I in dermal fibroblasts from patients with osteogenesis imperfecta (15,17,18). Surprisingly, loss of FKBP10 affected collagen levels not only on protein but also on transcript levels ( Figure 7A).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Figure 6C and 6D) as well as in decreased secreted collagen (Figure 8). In line with our results, deficiency of FKBP10 in osteogenesis imperfecta has been shown to attenuate collagen secretion and, moreover, decrease the extent of lysyl hydroxylation and extracellular collagen cross-linking and increase protease sensitivity of extracellular collagen I in dermal fibroblasts from patients with osteogenesis imperfecta (15,17,18). Surprisingly, loss of FKBP10 affected collagen levels not only on protein but also on transcript levels ( Figure 7A).…”
Section: Discussionsupporting
confidence: 88%
“…Surprisingly, loss of FKBP10 affected collagen levels not only on protein but also on transcript levels ( Figure 7A). This is unexpected, as FKBP10-as a chaperone and peptidyl-prolyl isomerase-is mainly ascribed a post-transcriptional role in procollagen I processing (11,14,15,17,18). Interestingly, loss of FKBP10 also attenuated the expression of the TGF-b-responsive genes PAI1 and a-SMA (Figures 6D and 7A).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a homozygous patient with HSP47 missense mutation, it was demonstrated that HSP47, potentially acting in cooperation with immunophilin FKBP65, encoded by FKBP10, is important for proper trafficking of type I procollagen to the Golgi [57]. Mutations in FKBP10 also cause moderately severe osteogenesis imperfecta [58,59] with decreased collagen cross-linking, resulting in sparsity and disorder of collagen fibril deposition [60].…”
Section: Potential Signaling Induced During Collagen Synthesis By Ostmentioning
confidence: 99%